Graduate school preparation from the Ronald E. McNair Postbaccalaureate Achievement Program: A systematic review (Higher Education Politics and Economics, 2019)
Underrepresented students attain a lower proportion of graduate degrees in the United States (US), demonstrating inequity in higher education. The Ronald E. McNair Post-baccalaureate Achievement Program has been providing underrepresented students with supports to increase their ability to attain a graduate degree. A systematic literature review identified that the Ronald E. McNair Post-baccalaureate Achievement Program promotes student growth in personal, social, and academic areas, as well as assist students enter graduate school. Few articles mentioned issues with the program but include students’ difficulties with socialization and the transition into graduate school. Limitations of the collected studies and possibilities for future research examining this program are included